Achievement of Meaningful Clinical Outcomes Is Unaffected by Capsulotomy Type During Arthroscopic Treatment of Femoroacetabular Impingement Syndrome: Results From the Multicenter Arthroscopic Study of the Hip (MASH) Study Group. Issue 3 (March 2021) - Parvaresh, Kevin; Rasio, Jonathan P.; Martin, RobRoy L.; Kivlan, Benjamin R.; Carreira, Dominic; Christoforetti, John J.; Harris, Joshua D.; Matsuda, Dean K.; Salvo, John; Wolff, Andrew B.; Nho, Shane J.
Background: Capsule management has emerged as an important topic in the field of hip arthroscopy. The 2 most popular techniques are interportal capsulotomy and T-type capsulotomy, but few studies have compared outcomes between these 2 techniques. Purpose: To compare 2-year (±2 months) patient-reported outcomes (PROs) between patients who underwent interportal versus T-type capsulotomy during arthroscopic labral repair for femoroacetabular impingement syndrome (FAIS). Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of a large multicenter registry of patients undergoing arthroscopic hip preservation surgery for FAIS was performed. Data from 9 surgeons across 9 sites between January 2014 and February 2018 were included in the study. Baseline demographic data, preoperative PROs, and minimum 2-year postoperative PROs including Hip Outcome Score–Activities of Daily Living (HOS-ADL), HOS–Sports Subscale (HOS-SS), modified Harris Hip Score, and International Hip Outcome Tool–12 (iHOT-12) were recorded. Patients were divided into 2 groups based on whether interportal or T-type capsulotomy was performed according to the senior surgeon's preference and training, and all capsulotomies were then routinely repaired. The 2 groups were matched 1:1 by age, sex, and body mass index (BMI). Achievement of minimal clinically important difference (MCID), Patient Acceptable Symptomatic State (PASS), and substantial clinical benefit (SCB) was compared for the HOS-ADL, HOS-SS, and iHOT-12 between the 2 groups. Results: The final analysis included 658 of 1483 eligible patients with a mean ± SD age of 32.6 ± 11.6 years and BMI of 24.0 ± 3.7; of these, 329 patients were treated via interportal capsulotomy, and 329 patients were treated via T-type capsulotomy. Female patients comprised 66.3% of the study population. Capsulotomy type was not a predictor of 2-year postoperative PROs on multivariate linear regression analysis when adjusted for covariates. Chi-square analysis showed no statistical difference in achievement of MCID, PASS, and SCB between the interportal and T-type groups for HOS-ADL (80.3%, 75.8%, 52.7% and 77.1%, 71.7%, 53.6%, respectively; P > .01 for all), HOS-SS (83.6%, 72.5%, 51.5% and 81.7%, 68.4%, 49.2%, respectively; P > .01 for all), and iHOT-12 (87.5%, 72.0%, 50.5% and 80.0%, 64.7%, 45.6%, respectively; P > .01 for all). Conclusion: Arthroscopic management of FAIS resulted in significant clinical improvement that was independent of capsulotomy type when the capsulotomy included repair.